A framework for designing behavioural change with the use of persuasive technology - Pintar, Ana (International journal of management, knowledge and learning, 2021)
Purpose: There is limited integration of behaviour theories and persuasive technology on behavioural change. Previous research calls for employing behaviour change theories to inform their persuasive designs and illustrate how the theories used are linked to the design features. This paper proposes integrating two theoretical models - the compelling system design and the transtheoretical model - to identify which persuasive interventions work best for the user to progress through different stages of behavioural change. Study design/methodology/approach: We performed an in-depth literature review of the transtheoretical model and persuasive system design, followed by an initial framework conceptualization. The initial framework was validated and finalized through in-depth interviews of individuals who have practiced the behaviour change for at least half a year. Findings: This paper has successfully identified the persuasive system design features and mapped them onto the transtheoretical model stages of change. The stages can be reduced into early and late stages. Consequently, we have developed a framework for designing behavioural change using persuasive technology and validated it through empirical research
Keywords: informacijsko-komunikacijska tehnologija; informatika; psihologija; uporabniki; vedenje